The The Influence of CSR Disclosure and Good Corporate Governance Towards Company’s Reputation - Herlina Lusmeida; Vanetta Betha Berlinda (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study examines the effect of CSR and GCG disclosure on the company's reputation. Measurement of CSR disclosure refers to the 2016 GRI Standards. GCG is measured by proxy for the size of the board of directors, gender diversity in the board, and board activity. The research sample was 66 companies during 2018-2020 with the criteria of being public companies and releasing annual reports, not included in the financial sector companies, this was due to the characteristics of different business activities, regulations, and financial ratios, including being winners of the Corporate Image Awards for three years. consecutive years of research, reporting financial statements in rupiah currency, not foreign currency, make annual reports and/or sustainability reports during the research period, containing information on CSR and CG activities. and data analysis was performed with multiple linear regression analysis using SPSS program. The results show that CSR disclosure has a significant positive effect on the company's reputation, the size of the board of directors has a significant positive effect on the company's reputation, gender diversity in the board has a significant positive effect on the company's reputation, and board activities have a significant positive effect on the company's reputation.